Potensi sumber air dan kearifan masyarakat dalam menghadapi risiko kekeringan di wilayah karst (Kabupaten Gunung Kidul, Provinsi Yogyakarta) - Juliadi Nugroho; Muhammad Zid; Mieke Miarsyah (Badan Kerjasama Pusat Studi Lingkungan (BKPSL) se-Indonesia bekerjasama dengan Pusat Penelitian Lingkungan Hidup IPB (PPLH-IPB), 2020)
Water is one of the main needs of life. Long term water shortages can cause disasters. Drought is one of the most common natural disasters that occur due to reduced rainfall and the geological structure of the soil. Gunung Kidul Regency is an area that often experiences drought due to geological soil structure in the form of karst. This study aimed to discuss the efforts undertaken to reduce the risk of drought in the Gunung Kidul Regency, Yogyakarta. This research used descriptive method with literature study approach. The results showed several efforts that could be implemented to minimize the risk of drought, namely making wells whose water sources come from underground rivers, utilizing springs and constructing rainwater reservoirs.